Hambatan Penerapan Pembelajaran Diferensiasi pada Anak Usia Dini: Studi Pustaka Kurikulum Merdeka - Evi Selva Nirwana; Monika Putri; Henny Kurnia Agustina; Mesi Junita Triani; Sendy Listari; Tesa Sofiya Nandha Lestari (JURNAL ARMADA PENDIDIKAN, 2026)
Differentiated learning is one of the main characteristics of the Independent Curriculum, particularly in Early Childhood Education (PAUD) levels, which have highly diverse student characteristics. Differentiation is designed to meet children's learning needs based on their individual readiness, interests, and learning profiles. However, in its implementation, differentiated learning still faces various obstacles. This study aims to analyze these obstacles through a literature review approach by reviewing differentiation theory books, national and international journal articles published between 2015 and 2025, and official Independent Curriculum documents. The analysis results indicate that the main obstacles include teachers' limited understanding of the concept of differentiation, administrative burdens and time constraints, a lack of facilities and a supportive learning environment, a suboptimal teacher-child ratio, minimal parental involvement, and a lack of professional training related to differentiation. These obstacles are interrelated and have a direct impact on the quality of planning and implementation of differentiated learning. This study emphasizes the need for strategies to strengthen teacher competency, improve infrastructure, and strengthen synergy between schools and families. The research findings are expected to serve as a reference for educators, school principals, and policy makers to optimize the implementation of differentiated learning within the Independent Curriculum framework.